2012
DOI: 10.1182/blood-2011-07-370031
|View full text |Cite
|
Sign up to set email alerts
|

High-dose melphalan and peripheral blood stem cell transplantation for light-chain amyloidosis with cardiac involvement

Abstract: High-dose melphalan (HDM) plus stem cell transplantation is an effective treatment for light-chain amyloidosis (AL), but is associated with high treatment-related mortality in patients with cardiac involvement. We studied 187 patients with cardiac involvement with AL who underwent HDM between 1996 and 2008. The median age was 57 years and the median time from diagnosis to HDM was 3.6 months. Half of the patients received reduceddose melphalan (100-160 mg/m 2 ). The median overall survival (OS) was 66 months, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 24 publications
5
71
1
2
Order By: Relevance
“…TRM following HDM/SCT in this current report was 4%, and was 8% for modified cardiac biomarker stage III disease (P ÂŒ 0.623). It did not correlate with serum albumin of o2.5 g/dL, which has been demonstrated by Madan et al 7 We attribute this low TRM to patient selection, optimal pre-and post-transplant supportive care, and the experience of multi-disciplinary team members. Patient selection was dependent upon an objective assessment of functional status, such as exercise oximetry, stair climbing and formal CPET.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…TRM following HDM/SCT in this current report was 4%, and was 8% for modified cardiac biomarker stage III disease (P ÂŒ 0.623). It did not correlate with serum albumin of o2.5 g/dL, which has been demonstrated by Madan et al 7 We attribute this low TRM to patient selection, optimal pre-and post-transplant supportive care, and the experience of multi-disciplinary team members. Patient selection was dependent upon an objective assessment of functional status, such as exercise oximetry, stair climbing and formal CPET.…”
Section: Discussionmentioning
confidence: 61%
“…In HDM/SCT, hematologic CR correlates with EFS, OS, cardiac response and reduction in cardiac biomarkers. 7,13 Patients who do not achieve a VGPR or have a less than 90% reduction in serum FLCs exhibit a much worse prognosis. 16,17 In our series, the hematologic CR rate was 27% by intention-to-treat analysis, which compares with 43% in all evaluable patients with AL amyloidosis treated with HDM/SCT in our previous series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that reduced dose of melphalan is only one prognostic factor for shorter OS in patients with light-chain amyloidsis who receive autologous transplantation. 19 Thus, the long-term followup is needed to evaluate this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AL-CA may see improvement in their survival of up to 12 years with appropriate chemotherapy. 5,6 The traditional treatment for TTR-CA is liver transplantation, with novel pharmacological agents under development. 7 In the face of these advances and prognostic implications of CA, it is essential to make the correct diagnosis using prompt and reliable non-invasive imaging modalities.…”
mentioning
confidence: 99%